ANALISIS ISI SIARAN BERITA KRIMINAL MENGENAI KASUS PELECEHAN SEKSUAL DI iNEWS TV SULSEL - Rifai , Fadilah; Majid, Abd; Idris, Muhammad (UNIVERSITAS MUSLIM INDONESIA, 2022)
Mass media is usually considered as the delivery of information. The essence of the function of the media as a messenger of information is news. News is a report about an event or opinion that chooses important, interesting value from some audiences. Events or opinions will not become news if they are not published through the mass media. In this case, the news raised in this study is the criminal news of sexual harassment cases in 2021 which aired on the iNews Sulsel television program, which will be analyzed by researchers using qualitative content analysis techniques, as well as collecting public responses about reporting cases of sexual harassment with qualitative descriptive methods. . The results of the study, it can be concluded that criminal news regarding cases of sexual harassment that aired on the South Sulawesi iNews television program in 2021 only broadcast one informant by focusing on police statements. And the audience has a response to the meaning of sexual violence based on the background of each informant, namely, parents, education, community/environment around them. Based on the audience's interpretation, the position of women in cases of sexual violence is a vulnerable party because women are considered as trigger objects. That is the important role of the media in providing information, especially regarding cases of sexual harassment so that it does not happen again or happens around us